Reduction in Diarrhea- and Rotavirus-related Healthcare Visits Among Children <5 Years of Age After National Rotavirus Vaccine Introduction in Zimbabwe. Issue 10 (October 2017) - Mujuru, Hilda A.; Yen, Catherine; Nathoo, Kusum J.; Gonah, Nhamo A.; Ticklay, Ismail; Mukaratirwa, Arnold; Berejena, Chipo; Tapfumanei, Ottias; Chindedza, Kenneth; Rupfutse, Maxwell; Weldegebriel, Goitom; Mwenda, Jason M.; et al.
Abstract : Background: In Zimbabwe, rotavirus accounted for 41%–56% of acute diarrhea hospitalizations before rotavirus vaccine introduction in 2014. We evaluated rotavirus vaccination impact on acute diarrhea- and rotavirus-related healthcare visits in children. Methods: We examined monthly and annual acute diarrhea and rotavirus test-positive hospitalizations and Accident and Emergency Department visits among children <60 months of age at 3 active surveillance hospitals during 2012–2016; we compared prevaccine introduction (2012–2013) with postvaccine introduction (2015 and 2016) data for 2 of the hospitals. We examined monthly acute diarrhea hospitalizations by year and age group for 2013–2016 from surveillance hospital registers and monthly acute diarrhea outpatient visits reported to the Ministry of Health and Child Care during 2012–2016. Results: Active surveillance data showed winter seasonal peaks in diarrhea- and rotavirus-related visits among children <60 months of age during 2012–2014 that were substantially blunted in 2015 and 2016 after vaccine introduction; the percentage of rotavirus test-positive visits followed a similar seasonal pattern and decrease. Hospital register data showed similar pre-introduction seasonal variation and post-introduction declines in diarrhea hospitalizations among children 0–11 and 12–23 months of age. Monthly variation in outpatient diarrhea-related visits mirrored active surveillance data patterns. At 2 surveillance hospitals, the percentage of rotavirus-positive visits declined by 40% and 43% among children 0–11 months of age and by 21% and 33% among children 12–23 months of age in 2015 and 2016, respectively. Conclusion: Initial reductions in diarrheal illness among children <60 months of age, particularly among those 0–11 months of age, after vaccine introduction are encouraging. These early results provide evidence to support continued rotavirus vaccination and rotavirus surveillance in Zimbabwe. Abstract : Supplemental Digital Content is available in the text.